PENGARUH PENGGUNAAN MODUL GUIDED INQUIRY TERHADAP KEMAMPUAN BERPIKIR KRITIS MAHASISWA STIKES PERINTIS PADANG - Marisa Marisa; Lisa Fradisa (Ta'dib, 2018)
This study aims to determine the effect of the use of guided inquiry learning modules on critical thinking skills of students and comparing critical thinking skills of students taught through guided inquiry learning modules and conventional learning models. This is an experimental research. The data of the research were obtained through a test, and observatio . The normality, homogeneity, and the difference between the two sets of data were computed using the SPSS 16.0 For Windows program. Questionnaire result data for each student is given a score according to a scale. Then, the average score per statement and the average total score were found out. The results showed that the guided inquiry learning module and conventional learning could significantly improve students' critical thinking skills and the improvement of critical thinking skills with the treatment of guided inquiry learning models was significantly better than conventional learning. And the results of students’ activity in the experiment class are better than that in the control class.